The Third Half: a positive psychoeducational program to promote well-being and mental health among early career researchers - Jiménez-Villamizar, María Paola; Tejada-Gallardo, Claudia; Becerra-Rojas, Angelica; Devoto-Araya, Maximiliano; Fernández-García, María; López-García, Rodrigo; Bonilla, Ivan; Tadić Vujčić, Maja; T. Mol, Stefan; Sanz-Ruiz, Antoni; et al. (Psychology, Society & Education, 2024)
The decreasing well-being among doctoral candidates, coupled with a high prevalence of distress problems, is a topic of increasing concern in the field of higher education and research policy. The present study aimed to replicate, implement, and evaluate the effectiveness of The Third Half, a multi-component psychoeducational program in doctoral students. To address the limitations of the pilot study, we conducted a non-randomized controlled study using a repeated measures pre-post design with a total of 97 participants (Mage = 32.5; SD = 8.23), of whom 26 participated in the experimental group. Results showed that Third Half program participants reported significant decreases in indicators of negative affect (F = 4.01; p = .04) and anxiety (F = 4.95; p = .02) compared to the general control group; in the matched sample analysis (n = 20) significant decreases were found in indicators of negative affect (F = 4.72; p = .03), anxiety (F = 4.09; p < .001), and depression (F = 4.95; p = .03). It is concluded that the Third Half program is an effective and implementable psychoeducational program to improve the skills of early-career researchers in wellness management.